Legal Protection for Children as Victims of Criminal Acts of Sexual or Molestation Committed by People Who Have Family Relations and Carried Out Continuously - Situmeang, Ria Debora (KnE Social Sciences, 2025)
Attention to children as the next generation has important relevance in the development of human civilization. The approach method used in this research is the normative legal approach method, namely research that positions law as a system of norms regarding the principles, standards, rules of statutory regulations, court decisions, agreements, and doctrines (teachings). Children are not only national assets, but also have the right to protection and be provided with basic rights as regulated in the 1945 Constitution and related regulations. With the ratification of the Convention on the Rights of the Child and the enactment of Law No. 35 of 2014, the state is committed to protecting children from various forms of violence and discrimination. However, the reality shows that children in Indonesia still face many challenges, such as being exposed to violence committed by those closest to them. Therefore, there is a need for attention and real action to create a safe environment for children in all aspects of life.